A new label technology for the detection of specific polymerase chain reaction products in a closed tube - Nurmi, Jussi (Oxford University Press, 2000)
A novel signal generation principle suitable for real time and end-point detection of specific PCR products in a closed tube is described. Linear DNA probes were labeled at their 5′-ends with a stable, fluorescent terbium chelate. The fluorescence intensity of this chelate is lower when it is coupled to single-stranded DNA than when the chelate is free in solution. The synthesized probes were used in the real time monitoring of PCR using a prototype instrument that consisted of a fluorometer coupled to a thermal cycler. When the probe anneals to a complementary target amplicon, the 5′→3′ exonucleolytic activity of DNA polymerase detaches the label from the probe. This results in an enhanced terbium fluorescence signal. Since terbium has a long excited state lifetime, its fluorescence can be measured in a time-resolved manner, which results in a low background fluorescence and a 1000-fold signal amplification. The detection method is quantitative over an extremely wide linear range (at least 10–10(7) initial template molecules). The label strategy can easily be combined with existing label technologies, such as TaqMan 5′-exonuclease assays, in order to carry out multiplex assays that do not suffer from overlapping emission peaks of the fluorophores.